ANALISIS GAYA BAHASA DALAM IKLAN KAMPANYE CALON GUBERNUR DAN CALON WAKIL GUBERNUR DKI JAKARTA TAHUN 2012 - Wahyuningsi, Endang (LPPM Universitas Muhammadiyah Sumatera Barat, 2016)
The purpose of this researched was to (1) describe the benefit of figure speech incampaign advertising of Governor and Vice Governor Candidat in DKI Jakarta 2012 atKompas, Republika, and Suara Pembaruan, (2) describe the benefit of rhetoric in campaignadvertising of Governor and Vice Governor Candidate in DKI Jakarta 2012 at Kompas,Republika, and Suara Pembaruan. This research is qualitative research that had contentanalysis. The data research was a sentence or speech in campaign advertising of Governor andVice Governor Candidate in DKI Jakarta 2012 at Kompas, Republika, and Suara Pembaruan.The results of this research showed two things. First, the utilization figure of speech incampaign advertising of Governor and Vice Governor Candidate in DKI Jakarta 2012 atKompas, Republika, and Suara Pembaruan gave the poetic elements and had metaphormeaning or had additional meaning. Second, utilization of rhetoric in campaign advertisingGovernor and Vice Governor Candidates in DKI Jakarta 2012 at Kompas, Republika, andSuara Pembaruan for delivering the meanings, explanation, pressing and ornaments directly,and also have impressed by reader.Kata kunci: language style, campaign advertising. Governor, and vice governor